TINJAUAN VIKTIMOLOGIS TENTANG ANAK SEBAGAI KORBAN DALAM PROSTITUSI ONLINE - Moch. Rizky Rachmadi; Saidil Adri (Journal of Innovation Research and Knowledge, 2025)
This study aims to deeply analyze the position of children as victims in online prostitution practices through a victimology approach. The research method used is normative legal research, which focuses on the study of the principles, norms, and provisions of positive law governing the protection of children from sexual exploitation. This approach also examines the gap between das sollen and das sein, namely the difference between legal norms that should provide optimal protection for children and the reality of their implementation in the field, which is often still ineffective. The results show that the development of digital technology has changed the pattern of prostitution practices from conventional forms to online application-based ones such as Michat, Tinder, Tantan, WhatsApp, and Facebook. This transformation makes children increasingly vulnerable to becoming objects of sexual exploitation through online recruitment, manipulation, and coercion mechanisms. From a victimology perspective, children are categorized as completely innocent victims and socially weak victims because they lack the capacity to provide valid consent, are vulnerable to external influences, and experience economic, psychological, and social dependence. These findings emphasize the importance of strengthening mechanisms for protection, prevention, and recovery of victims that support the principles of child protection and restorative justice.